Evaluation of mangosteen peel extract in the kato-katz technique for enhanced visualization of helminth eggs - Tanjung, Asbar; Maulidayanti, Sharfina; Br Situmorang, Ing Mayfa (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Mangosteen rind (Garcinia mangostana) contains anthocyanins, which have potential as natural dyes. One promising application is as a substitute for malachite green in the Kato-Katz technique, a fecal examination method used to detect helminth eggs such as Ascaris lumbricoides. Objectives: To evaluate the effectiveness of mangosteen peel extract at various concentrations (25%, 50%, 75%, and 100%) as an alternative staining agent in the Kato-Katz method. Materials and Methods: This laboratory-based experimental study utilized fecal samples positive for A. lumbricoides, which were examined using the Kato-Katz method with selophane tape soaked in mangosteen rind extract. Observed parameters included egg count per gram of feces (epg), clarity of egg morphology, and background contrast under the microscope. Results: The 75% concentration yielded the best performance, with optimal background staining, clear egg morphology, and the highest average egg count (853 eggs per gram). Concentrations of 25%, 50%, and 100% showed lower effectiveness. Conclusions: A 75% concentration of mangosteen rind extract is effective as a natural dye substitute for malachite green in the Kato-Katz method, providing good visual contrast and supporting accurate identification of helminth eggs